Daya Dukung Lingkungan Tambak di Kecamatan Pulau Derawan dan Sambaliung, Kabupaten Berau, Provinsi Kalimantan Timur [Carrying Capacity for Brackishwater Pond in The Derawan Islands and Sambaliung Sub-Districts, Berau Regency, East Kalimantan Province] - Erna Ratnawati; A. Indrajaya Asaad (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract Carrying capacity for brackishwater pond is the main concept to be developed for the management of natural resources and the environment in a sustainable manner, it also should be applicated in Berau Regency. A study had been conducted to determine the carrying capacity of brackishwater ponds in the Derawan Islands and Sambaliung sub-districts, Berau. Considered factors in the analysis of environmental carrying capacity is the topography and hydrology, soil conditions, water quality and climate condition. Weighting system had been used as analysis of the carrying capacity which refers to the modification of Poernomo (1992). The study showed that the carrying capacity in those two sub-districts was similar, which was 62.52% respectively, so the ponds' area that can be supported were : 2,915.62 and 304.90 ha. The main factors that cause low carrying capacity for brackishwater pond in study area were the high potential soil acidity, high content of toxic elements, low nutrient and high rainfall.